Predictors of mammography based on Health Belief Model in Khorramabad women - Zahra Khazir; Mohammad Ali Morrowati Sharifabad; Ali Akbar Vaezi; Behnaz Enjezab; Hossein Fallahzadeh; Fatemeh Yari (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Health beliefs play an important role in people's willingness to participate in health-promoting behaviors. Given the role of beliefs in women's function and the importance of the benefits of mammogram, and because the predictors of a behavior are a major prerequisite to codification of an effective prevention program, the present study was conducted with the aim of predicting mammography based on Health Belief Model (HBM) in women in Khorramabad. Materials and Methods: In this cross-sectional study, 262 women referring to health centers in Khorramabad, Lorestan province, in 2018, were selected by randomly sampling. The data collection tool was a four-part questionnaire including demographic information, knowledge on breast cancer and mammography, Champion's Health Belief Model, and Champion's Self-Efficacy Questionnaire for Mammography. Validity and reliability of the tool were investigated and confirmed. Data were analyzed by version 16 of SPSS software using descriptive statistics, Chi-squared test, and multiple logistic regression. RESULTS: The mean (standard deviation) age of the participants was 49.26 (±7.79) years. Seventy-nine (30.85%) of the 262 participants reported mammography. Constructs' sensitivity, benefits, barriers, and perceived self-efficacy were significantly different in terms of performing mammography (P < 0.05). Participants with a history of breast cancer (odds ratio [OR] = 11.18, 95% confidence interval [CI] = [3.73-33.46]) had lower perceived barriers (OR = 3.54, 95% CI= [1.77-7.09]), were more likely to undergo mammography than women with no family history of breast cancer, and had moderate-to-high perceived barriers (P < 0.001). CONCLUSION: The results of this study indicate that health managers are required to pay more attention to training and promoting screening methods. Understanding the barriers to mammography in women by managers can help design and implement effective programs that enhance mammography in women.